2008
DOI: 10.1101/gr.076208.108
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the amphioxus genome on the origin of vertebrate neural crest

Abstract: The emergence of the neural crest has been proposed to play a key role in early vertebrate evolution by remodeling the chordate head into a “new head” that enabled early vertebrates to shift from filter feeding to active predation. Here we show that the genome of the basal chordate, amphioxus, contains homologs of most vertebrate genes implicated in a putative neural crest gene regulatory network (NC-GRN) for neural crest development. Our survey of gene expression shows that early inducing signals, neural plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
140
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 37 publications
0
140
1
1
Order By: Relevance
“…2, more detailed expression patterns are shown in Figs. S3-S7) (8,9). Interestingly, only FGF8/17/18, FGFA, and FGFE show transient expression in the presumptive mesoderm.…”
Section: Resultsmentioning
confidence: 97%
“…2, more detailed expression patterns are shown in Figs. S3-S7) (8,9). Interestingly, only FGF8/17/18, FGFA, and FGFE show transient expression in the presumptive mesoderm.…”
Section: Resultsmentioning
confidence: 97%
“…These findings suggest that initial formation of the neural plate border may occur via a mechanisms conserved between cephalochordates and vertebrates. Support for this idea comes from experimental manipulations in which inhibition of BMP signaling has similar effects in amphioxus as in vertebrates (Yu et al, 2008).…”
Section: Nonvertebrate Chordatesmentioning
confidence: 99%
“…Recently, a more comprehensive functional analysis of multiple components with the network was systematically tested in a single species (7). The results suggested that much of the NC-GRN is highly conserved across vertebrates (7), contrasting with nonvertebrate chordates (6,(8)(9)(10)(11)(12)(13)(14)(15), which appear to lack a module involved in neural crest specification (16). However, proximal portions of this network appear conserved to the base of the chordate lineage (17).…”
mentioning
confidence: 99%